2020
DOI: 10.1371/journal.pone.0228372
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare practitioners’ views of social media as an educational resource

Abstract: Social media is increasingly utilized as a resource in healthcare. We sought to identify per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 33 publications
0
55
0
5
Order By: Relevance
“…ODH is about more than supporting data management. ODH provides learning opportunities to citizens, so that they can protect and take care of themselves when they share personal data on social networks [ 57 - 59 ]. At its core, ODH teaches people how to differentiate between real and fake news, which are disseminated over the mass media and the internet.…”
Section: The Five Dimensions: the Essential Fabric Of Interconnectionmentioning
confidence: 99%
“…ODH is about more than supporting data management. ODH provides learning opportunities to citizens, so that they can protect and take care of themselves when they share personal data on social networks [ 57 - 59 ]. At its core, ODH teaches people how to differentiate between real and fake news, which are disseminated over the mass media and the internet.…”
Section: The Five Dimensions: the Essential Fabric Of Interconnectionmentioning
confidence: 99%
“…The two matrices provided by Mallet are used for providing a graph representation allowing us in next step to handle the topics-words based graph through graph processing tools. This module is implemented using python and NetworkX 14 which is a Python package for the creation, manipulation, and study of the structure, dynamics, and functions of complex networks and it is distributed as open source 3clause BSD license. This module generates a file GEXF 15 (Graph Exchange XML Format).…”
Section: Building Graph Representationmentioning
confidence: 99%
“…Content provided by the user is growing during disasters in comparison with the normal situation. Therefore, the analysis of the such as epidemic virus spreading [12], prediction of the contagious population behaviour and accurate detection and identification of professionally unreported drug side effects using widely available public data (open data) [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A recent report concluded that only 43% of healthcare practitioners who own social media accounts would utilise them for educational purposes, with the probability significantly decreasing in those ≥40 years old. 8 Additionally, in a survey encompassing more than 4,000 physicians, more than 90% of physicians reported the use of social media for personal activities. However, only 65% reported use of such platforms for professional purposes.…”
mentioning
confidence: 99%